Expression Levels of Some Antioxidant and Epidermal Growth Factor Receptor Genes in Patients with Early-Stage Non-Small Cell Lung Cancer - De Palma, Giuseppe; Mozzoni, Paola; Acampa, Olga; Internullo, Eveline; Carbognani, Paolo; Rusca, Michele; Goldoni, Matteo; Corradi, Massimo; Tiseo, Marcello; Apostoli, Pietro; Mutti, Antonio (Journal of Nucleic Acids, 2010)
This study was aimed at: (i) investigating the expression profiles of some antioxidant and epidermal growth factor receptor genes in cancerous and unaffected tissues of patients undergoing lung resection for non-small cell lung cancer (NSCLC) (cross-sectional phase), (ii) evaluating if gene expression levels at the time of surgery may be associated to patients' survival (prospective phase). Antioxidant genes included heme oxygenase 1 (HO-1), superoxide dismutase-1 (SOD-1), and -2 (SOD-2), whereas epidermal growth factor receptor genes consisted of epidermal growth factor receptor (EGFR) and v-erb-b2 erythroblastic leukaemia viral oncogene homolog 2 (HER-2). Twenty-eight couples of lung biopsies were obtained and gene transcripts were quantified by Real Time RT-PCR. The average follow-up of patients lasted about 60 months. In the cancerous tissues, antioxidant genes were significantly hypo-expressed than in unaffected tissues. The HER-2 transcript levels prevailed in adenocarcinomas, whereas EGFR in squamocellular carcinomas. Patients overexpressing HER-2 in the cancerous tissues showed significantly lower 5-year survival than the others.